2012
DOI: 10.1155/2012/354145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combining Therapy with Traditional Chinese Medicine-Based Psychotherapy and Herbal Medicines in Women with Menopausal Syndrome: A Randomized Controlled Clinical Trial

Abstract: This multicenter, randomized, controlled clinical study was designed to address the effectiveness of combined traditional-Chinese-medicine- (TCM-) based psychotherapy and Chinese herbal medicine (CHM) in the treatment of menopausal syndrome. Altogether 424 eligible women diagnosed as menopausal syndrome and categorized as Kidney-Yin/Kidney-Yang deficiency pattern in TCM were randomly assigned into 4 groups and accepted TCM-based psychotherapy (PSY), CHM, PSY + CHM, or placebo therapies, respectively, for 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In an attempt to identify the active chemical constituents of the MPG formula that may be responsible for these effects on granulosa cells, we have investigated some of the primary chemical compounds present in M. alba fruits. The main flavonoid glycosides include quercetin, astragalin, isoquercetin and rutin [16,17,18]. In this work, we demonstrate that purified astragalin (kaempferol-3- O -glucoside; Figure 1), a flavonoid glycoside that isolated from M. alba (white mulberry fruit) one of the herbal constituents of the TCM formula for menopause reduces ovarian GC apoptosis in vitro and in vivo and reverses ovarian failure in an aged female rat model of menopause.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…In an attempt to identify the active chemical constituents of the MPG formula that may be responsible for these effects on granulosa cells, we have investigated some of the primary chemical compounds present in M. alba fruits. The main flavonoid glycosides include quercetin, astragalin, isoquercetin and rutin [16,17,18]. In this work, we demonstrate that purified astragalin (kaempferol-3- O -glucoside; Figure 1), a flavonoid glycoside that isolated from M. alba (white mulberry fruit) one of the herbal constituents of the TCM formula for menopause reduces ovarian GC apoptosis in vitro and in vivo and reverses ovarian failure in an aged female rat model of menopause.…”
Section: Introductionmentioning
confidence: 69%
“…Since 2008 we have been investigating a TCM herbal formula Menoprogen (MPG) [14,15,16,17,18,19], which has been shown to reduce menopausal symptoms and the Kupperman index in Chinese women [15]. This formula contains five medicinal and food plants, and has been used in China for centuries to treat menopausal symptoms [14,15,16,17,18,19]. In our previous work, we have shown that the mechanism of MPG is very novel in that it does not act as a phytoestrogen, but works indirectly by reducing GC apoptosis via a mechanism involving IGF-1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations